Hemorrhagic fever in adults at Pathumtani hospital - พืชไพจิตร, วันทนา (Disease Control Journal, 2014)
Background: Hemorrhagic fever is an infectious disease which has been an important public health problem in Thailand and in many countries worldwide. Dengue viruses are transmitted to humans through the bite of infected Aedes mosquitos, principally, Aedesaegypti. This fever have progressively increased and distribution in Thailand and also in Pathumtani province. The objective was to describe the characteristic of dengue outbreak among dengue fever (DF) patients and dengue hemorrhagic fever (DHF) patients and to implement specific control and prevention. Populations were 283 hemorrhagic fever patients, admitted to outpatient clinics at Pathumtani Hospital during the period October 1, 2012 - March 31, 2013. This study was a retrospective and collected data frommedical record. Descriptive statistics was used for statistical analysis. Results: Total 283 cases were met case definition in 125 DF and 158 DHF. Male:female ratio was 1.3:1 in DF and 1.1:1 in DHF patients. Average age was 26.6±3.8 and 32.6±4.6 years and age between 15-19 years was the highest proportion. Student was the highest affected. There were different times to see doctors, within 3 days of illness for DF and 5 days of illness for DHF patients. The most common clinical features of DF patients were fever, myalgia, headache, and cough whereas in DHF patients were fever, nausea/vomiting, abdominal pain, myalgia, and some cases had skin haemorrhages (petechiae). Both DF and DHF patients with thrombocytopenia (100,000 cells/mm3 or less) and leukopenia (5,000 cells/ mm 3 or less) were the highest proportion occurred within 1 day of subsidence of fever. Plasma leakage due to increased haemoconcentration manifested by a rise in the hematocrit in male was greater than female and was highest a rising hematocrit occurred within 1 day of subsidence of fever. The largest DHF patients was grad II of severity.